The impact of saltwater intrusion on the crop areas at Pantai Punggur, Batu Pahat, Johor - Zulkifli, N F Mohd; Musa, S; Azmi, N A Nabihah; Ahmad Uma, M H
Saltwater intrusion has been a growing issue affecting coastal communities throughout the ages. Most agricultural land globally is located in low-lying coastal regions that have been reclaimed. The stability and resilience of a microbial community play a crucial role in determining how soil reacts to and recovers from environmental challenges. However, land response to periodic coastal flooding and salt stress was studied in this study. The study has been conducted around Pantai Punggur, Batu Pahat. The soil sample was collected from different salinity levels, based on 0% serving as the control group and other salinity levels of 1.6%, 2.0%, and 2.4%. Soil samples were tested in the laboratory based on the soil salinity level and microbial activities. This laboratory test found that the electrical conductivity (EC) value range is 0.0035 dS/m to 1.297 dS/m, while for the pH value range is pH 7.27 to pH 7.52, there are also 20% microbial activities in the soil. Using gypsum as a soil amendment can reduce saline water in the soil by 15% to 25%. In conclusion, this experimental study helps minimize soil salinity and improve soil structure based on the existing literature on saltwater intrusion's impact on alkaline soil's agricultural fertility